Loss of BRCA1 Spontaneously Induces the Tumorigenesis in Lacrimal Gland. (17th December 2018) - Kim, Sun Eui; Baek, Hye Jung; Park, Eun Jung; Lim, Sung Chul; Kim, Sang Soo
Abstract : Environmental and genetic factors exert important influences on lifespan and neoplastic transformation. We have previously shown that spontaneous tumors form frequently in mice homozygous for a full-length Brca1 deletion. In general, mutations of BRCA1 are closely associated with induction of breast and ovarian cancers but are also known to contribute to the incidence of other cancers at a low frequency. Female Brca1 -mutant mice ( Brca1 co/co MMTV-cre ) were generated by crossing Brca1 conditional knockout mice and MMTV-cre mice, and the occurrence of lacrimal gland abnormalities and tumors was followed until mice reached 18 months of age. Lacrimal gland tumors, which occur at a very low frequency in the human population (1 per 1, 000, 000 per year), were detected in 7 cases of Brca1 co/co MMTV-cre mice (2.75%) older than 9 months of age. None of seven mice exhibited any abnormality in the mammary gland including neoplasia, suggesting lacrimal gland tumor is spontaneously and independently formed. These tumors, which were detected in seven mutant mice that displayed exophthalmoses, were malignant, originated from epithelial cells, and were identified as acinic cell carcinoma by pathological analysis. Further analysis revealed that tumorigenesis was accompanied by the accumulation of cyclin D1 and decreased expression of the cellular oncogenes, c-Myc, c-Jun, and c-Raf. Tumors also exhibited rearrangement of cytoskeletal proteins, including β -catenin, keratin 5, and vimentin, depending on tumor progression. These results suggest that BRCA1 is involved in genetic stability of the lacrimal gland, providing new insight into genomic instability in organism maintenance and tumorigenesis of the lacrimal gland.